(untitled) (Comillas Journal of International Relations, 2020)
Rape has been used as a tool of war throughout the history of mankind. With the establishment of the International Criminal Court, rape was included in the Rome Statute, being internationally recognized as a war crime, a crime against humanity and a means to commit genocide. The Islamic State of Iraq and Syria, in its war to establish the caliphate, has carried out a campaign of sexual violence against women of religious minorities such as the Yazidi. This article examines the evolution of the definition of rape in International Criminal Law and applies the current definition to the crimes committed by ISIS against the Yazidi. The study assesses the elements of the actus reus of genocide and considers that the actions carried out by the Islamic State towards the Yazidi could qualify as a genocide by means of rape.